Evaluation of HPV Genotyping Assays for Archival Clinical Samples - Lillsunde Larsson, Gabriella; Carlsson, Jessica; Karlsson, Mats G; Helenius, Gisela (The Journal of molecular diagnostics : JMD, 2015)
Human papillomavirus (HPV) testing and genotyping of FFPE tissue samples is important in epidemiological investigations. Here, we compare four different HPV genotyping methods for use in FFPE clinical samples. Comparative testing was performed on 99 samples with a clinical suspicion of HPV. Specimens were analyzed with Anyplex II HPV28 detecting 28 genotypes using real-time PCR and melting curve analysis, CLART HPV2 detecting 35 genotypes using PCR and microarray detection, and MGP5+/6+ consensus primer system together with pyrosequencing. Results were compared to a real-time PCR reference protocol detecting 14 genotypes. In total, 68% of the samples were positive for an HPV genotype using the reference protocol and MGP5+/6+ primer system. Anyplex II HPV28 analysis and CLART HPV2 had 82% and 72% positive samples, respectively. All four methods showed good agreement when comparing the 14 genotypes included in the reference protocol. When evaluating all genotypes, the Anyplex II HPV28 assay and the CLART assay changed the status of the sample (individually or together) from negative with respect to the reference protocol to positive for either a Group 1 (n = 4) or Group 2 (n = 6) genotype. We conclude from this study that for an extended genotyping approach with a high sensitivity for FFPE specimens, both the Anyplex II HPV28 and CLART HPV2 assays are suitable alternatives despite minor intra-assay differences.